Cologenderism and Gender Equality: A Gift, a Right or a Privilege? - Ikegbu, Ephraim A.; Iwuagwu, Emmanuel K.; Ariche, Chrisantus K. (Program Studi Sosiologi, 2020)
Arguments as to the status of women in political, economic, social and religious spheres of life have dominated contemporary narratives and had given birth to different schools of thought all in attempt to nip in the bud, the growing consequences of this social construct. There have been psychological and emotional feelings of distrust, marginalization and oppression echoed by the female gender against the male gender. The female gender nursed some sense of inferiority and uniqueness in her conducts, interaction and relationship with the male gender. The male carries itself as the alter ego, and feels high-level superiority and in command of the ‘estates’. This x-rayed circumstance has given rise to feminism and its varying shades, all geared towards the protection and preservation of the rights of women, and advancing for equality in all respects. Cologenderism which seeks to balance the arguments of both sexes by arguing that both sexes can marginalize and be marginalized, oppress and be oppressed, subjugate and be subjugated depending on statistical structuring in a particular circumstance, in this context, posits that equality contest or demand between sexes should not be categorized as gift or privileges. This paper using analytical, rational, expository and critical methods, argues that equality is a right for both sexes and, therefore, should be contested and struggled for with consistency and available mental talents until it is achieved.